An empirical examination of the determinants of audit report delay in France. Issue 8 (3rd September 2018) - Khoufi, Nouha; Khoufi, Walid
Abstract : Purpose: This study aims to investigate the determinants of delay in publishing audited reports. Design/methodology/approach: The research is conducted on a sample of French listed companies, covering the period of five years (from 2010 to 2014). The authors use pooled ordinary least squares regression analysis, modeling audit delay as a function of the following explanatory variables relating to the attributes of companies and their auditors. Findings: A statistically significant association is found between audit delay and type of audit firm, audit opinion, firm size, the month of year-end and profitability. The results suggest that audit delay lag is reduced by appointing an international audit firm but is extended by aspects of qualified audit opinion. Originality/value: The contribution of this paper is to investigate audit report in a developed capital market by taking advantage of access to proprietary data on audit timing and audit opinion. This allowed to overcome some of the problems of data quality that inhibit importing research methods from France to other advanced capital markets.